PERFORMA PRODUKSI BEBERAPA GALUR AYAM BURAS YANG DIBERI JAMU FERMENTASI - Astri Dwiyanti Tagueha; Isye Jean Liur; Rajab Rajab (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
The aim of this research was to known strain effects’ on native chicken supplemented with fermented herbs. Sixty four chicken were arranged into Completey Randomized Design which divide into four treatment, i.e :G1(native), G2 (Bangkok), G3 (KUB), G4 (Bangkok). Obtained variabels for analysis were feed intake, water intake, weight gain, feed conversion ratio, and mortality rate. The result show that the average of production performance respectively : feed intake (gr/tail) : 3967.1 (G1); 3664.21(G2); 4102.36 (G3); 3942(G4), whereas weight gain (gr/tail) : 616.5 (G1); 556.46 (G2); 619.02 (G3); 637.27 (G4). Four strain has >6 in feed convertion rate and > 5% in mortality rate.